A Prognostic Tool for Individualized Prediction of Graft Failure Risk within Ten Years after Kidney Transplantation. (8th April 2019) - Stamenic, Danko; Rousseau, Annick; Essig, Marie; Gatault, Philippe; Buchler, Mathias; Filloux, Matthieu; Marquet, Pierre; Prémaud, Aurélie
Abstract : Identification of patients at risk of kidney graft loss relies on early individual prediction of graft failure. Data from 616 kidney transplant recipients with a follow-up of at least one year were retrospectively studied. A joint latent class model investigating the impact of serum creatinine (Scr) time-trajectories and onset of de novo donor-specific anti-HLA antibody ( dn DSA) on graft survival was developed. The capacity of the model to calculate individual predicted probabilities of graft failure over time was evaluated in 80 independent patients. The model classified the patients in three latent classes with significantly different Scr time profiles and different graft survivals. Donor age contributed to explaining latent class membership. In addition to the SCr classes, the other variables retained in the survival model were proteinuria measured one-year after transplantation (HR=2.4, p=0.01), pretransplant non-donor-specific antibodies (HR=3.3, p<0.001), and dn DSA in patient who experienced acute rejection (HR=15.9, p=0.02). In the validation dataset, individual predictions of graft failure risk provided good predictive performances (sensitivity, specificity, and overall accuracy of graft failure prediction at ten years were 77.7%, 95.8%, and 85%, resp.) for the 60 patients who had not developed dn DSA. For patients with dn DSA individual risk of graft failure was not predicted with a so good performance.